Chemical composition and biological activities of Helicteres vegae and Heliopsis sinaloensis - Sandra Olivas-Quintero; Gabriela López-Angulo; Julio Montes-Avila; Sylvia Páz Díaz-Camacho; Rito Vega-Aviña; José Ángel López-Valenzuela; Nancy Yareli Salazar-Salas; Francisco Delgado-Vargas (Taylor & Francis Group, 2017)
Context: Helicteres vegae Cristóbal (Sterculiaceae) (Hv) and Heliopsis sinaloensis B.L. Turner (Asteraceae) (Hs) are endangered and poorly studied plant species; related plants have been used against chronic-degenerative and infectious diseases. Therefore, Hv and Hs could be sources of bioactive compounds against these illnesses. Objective: To determine the chemical composition and biological activities (antioxidant, antimutagenic and antimicrobial) of Hv and Hs leaves (L) and stems (S). Materials and methods: Methanol extracts (ME) of each plant/tissue were evaluated for their phytochemicals; phenolics (HPLC-DAD-ESI-MS); antioxidant activity (AA) (0.125-4 mg/mL) (DPPH, ABTS, ORAC and β-carotene discoloration); antimutagenicity (0.5 and 1 mg/plate) (Ames assay, tester strain Salmonella enterica serovar Typhimurium YG1024, 1-nitropyrene as mutagen); activity against human pathogens (1 mg/mL); and toxicity (0.01-2 mg/mL) (Artemia salina assay). Results: All ME showed flavonoids and triterpenes/steroids. The ME-SHv had the highest content of total phenolics (TP) (2245.82 ± 21.45 mg GAE/100 g d.w.) and condensed tannins (603.71 ± 1.115 mg CE/100 g d.w.). The compounds identified were flavonoids (kaempferol 7-O-coumaroylhexoside, and two kaempferol 7-O-rhamnosylhexosides) and phenolics [rosmarinic acid, and 3'-O-(8"-Z-caffeoyl) rosmarinic acid]. The ME-LHs showed the highest content of flavonoids (357.88 mg RE/g d.w.) and phenolic acids (238.58 mg CAE/g d.w.) by HPLC. The ME-SHv showed the highest AA. All ME were strong antimutagens (63.3-85.7%). Only the Hs extracts were toxic (ME-LHs, LC50 = 94.9 ± 1.7 μg/mL; ME-SHs, LC50 = 89.03 ± 4.42 μg/mL). Discussion and conclusions: Both Hv and Hs are potential sources of preventive and therapeutic agents against chronic-degenerative diseases.